Hunters and herders: Exploring the Neolithic transition in the rock art of Shuwaymis, Saudi Arabia. (December 2015) - Guagnin, Maria; Jennings, Richard P.; Clark-Balzan, Laine; Groucutt, Huw S.; Parton, Ash; Petraglia, Michael D.
Abstract: In Arabia the transition to a Neolithic economy is thought to be characterised by a shift to mobile pastoralism, rather than the traditional icons of the Neolithic such as sedentism and crop cultivation. However, in the absence of detailed archaeological research, the Early Holocene prehistory of central, northern and northwestern Saudi Arabia remains largely unknown. Here we use the engraved rock art recorded on 254 panels in Shuwaymis, Ha'il Province, and in particular depictions of hunting and herding scenes, to identify evidence on the character of the Neolithic transition in the region. Due to high levels of erosion it was not possible to carry out spatial analysis of the sites. However, the content and stratigraphic relationship of hunting and herding panels, re-engraving events, and cultural markers related to human figures were analysed. The results show that the engravings can be divided into an exclusive hunting period, where equids are frequently being hunted. Domestic cattle are often placed over and integrated into existing hunting scenes by re-engraving parts of the scene and turning hunting figures into herding figures. Cultural markers associated with human depictions such as headdresses and possible penis sheaths continue across both periods. The evidence in the rock art indicates that herding was adopted by local hunters. Moreover, the rock art shows that herders identified with the depicted hunters and that ibex hunting remained part of the image repertoire, and potentially of the subsistence economy, throughout the Holocene.